ANALISI KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATERI SEBARAN FLORA DAN FAUNA INDONESIA DAN DUNIA KELAS XI SMA NEGERI 3 PADANG - Rusdi Arief; Ernawati Ernawati (JURUSAN GEOGRAFI FIS UNP, 2021)
ABSTRACT This study aims to (1) determine the analysis of the needs of interactive learning media based on Android in the teaching and learning process (2) Knowing the ease of use of Geography learning media applications in class XI SMA Negeri 3 Padang. This research is a quantitative descriptive study, the research subjects are students of class XI IPS in Geography subject at SMA Negeri 3 Padang. The instrument used was a questionnaire, compiled using the help of google form and distributed through the class WhatsApp Group application. The sampling technique used Total Sampling with a total of 68 students as respondents. The results of this study indicate that the application of learning media based on Android GEO Explorer which is made has the highest priority frequency needs of 68 students, namely 45 students with a percentage of 66.17% in the